Caffeic acid phenethyl ester (CAPE) protects rat skeletal muscle against ischemia-reperfusion-induced oxidative stress - Ozyurt, Huseyin; Ozyurt, Birsen; Koca, Kenan; Ozgocmen, Salih (Elsevier Science Inc, 2007)
Oxygen-derived free radicals have been implicated in the pathogenesis of skeletal muscle injury after ischemia-reperfusion. Caffeic acid phenethyl ester, an active component of propolis extract, exhibits antioxidant properties. The aim of this study was to assess the effects of caffeic acid phenethyl ester (CAPE) and alpha-tocopherol (vit E) on ischemia/reperfusion (I/R) injury in a rat hind limb ischemia/reperfusion model. For this purpose, ischemia was induced in anesthetized rats by unilateral (right) femoral artery clipping for 2 h followed by 2 h of reperfusion. Four groups were studied: sham, I/R, I/R + CAPE and I/R + vit E. Drugs were administered intraperitoneally after I h of ischemia and I/R rats received saline vehicle. After 2 h of reperfusion, venous blood was sampled and the right gastrocnemius muscle was harvested. Plasma and tissue were assayed for malondialdehyde (MDA), superoxide dismutase (SOD) and nitric oxide (NO) metabolites. Tissue was also assayed for catalase (CAT) activity. Both tissue and plasma NO levels, MDA levels, SOD activities was significantly increased in I/R groups compared to control groups. The two treated groups showed decreased MDA and NO in both muscle and plasma compared to the I/R group. No differences were noted in muscle tissue SOD in three I/R groups, but SOD activity were increased in the plasma of I/R + CAPE and I/R + vit E groups compared with I/R group. Whereas tissue CAT activity was not changed among groups. Our results indicate that CAPE has antioxidant properties similar to those of vit E in this model and may attenuate the harmful effects of hind limb I/R in skeletal muscle. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: reperfusion injury; skeletal muscle; caffeic acid phenethyl ester (CAPE); alpha-tocopherol; oxidative stress